Different Effects of Endothelial Extracellular Vesicles and LPS-Induced Endothelial Extracellular Vesicles on Vascular Smooth Muscle Cells: Role of Curcumin and Its Derivatives - Xiang, Debiao; Li, Yamei; Cao, Yuling; Huang, Ying; Zhou, Lili; Lin, Xiulian; Qiao, Yong; Li, Xin; Liao, Duanfang (Frontiers in Cardiovascular Medicine, 2021)
Background: During the progression of atherosclerosis (AS), the vascular endothelial and smooth muscle cells are reciprocally regulated by extracellular vesicles (EVs). EVs have different effects on pathological and physiological processes due to the different cargoes contained in EVs. Purpose: To study the effects of endothelial cells-derived EVs on normal and inflammatory conditions. To investigate the effects of curcumin and curcumin derivatives (Nicotinic-curcumin) on endothelial EVs. Methods: EVs were isolated from human umbilical vein endothelial cells (HUVECs) by ultracentrifugation. To examined the effect of normal and LPS-induced endothelial cells-derived EVs on the proliferation of human aortic smooth muscle cells (HASMCs), the CCK-8 assay was performed. Transwell and wound healing assays were conducted to assess cell migration. The effects of EVs on lipid accumulation following treatment with oxidized low-density lipoprotein (Ox-LDL) were evaluated with the oil red O staining assay and HPLC. The number of EVs was calculated using the nanoparticle tracking analysis (NTA) and BCA. The expression levels of Rab27a and Rab27b that regulate the EVs secretion were measured by Western blotting assay. The differential expression of miRNAs in endothelial EVs and LPS-induced endothelial EVs was analyzed using miRNA-Sequencing (miRNA-Seq) and RT-PCR. Results: Treatment with endothelial EVs reduced the proliferation and migration of HASMCs as well as lipid accumulation in HASMCs. However, treatment with LPS-induced endothelial EVs did not inhibit the migration of HASMCs or lipid accumulation, instead it promoted the proliferation of HASMCs. Treatment with the two types of EVs induced differential expression of several miRNAs, including miR-92a-3p, miR-126-5p, miR-125a-3p, miR-143-3p, etc. Moreover, 1 μg/mL LPS induction greatly increased secretion of endothelial EVs. Treatment with curcumin and nicotinic-curcumin reduced endothelial EVs secretion, possibly by inhibiting inflammation. Conclusion: Endothelial EVs may confer beneficial effects on atherosclerosis by regulating vascular smooth muscle cell (VSMCs), whereas pro-inflammatory factors may disrupt this effect.